Antioxidant Activity of Syzygium polyanthum Extracts - Mutia Devi Hidayati; Taslim Ersam; Kuniyoshi Shimizu; Sri Fatmawati (Indonesian Journal of Chemistry, 2017)
Antioxidant activities of Syzygium polyanthum leaves extracts (methanol, ethyl acetate, dichloromethane and n-hexane) were evaluated by using DPPH (2,2-diphenyl-2-picrylhydrazyl) and ABTS (2,2’-azinobis (3-ethylbenzothiazole-6-sulfonic acid) methods. The methanol extract showed the highest antioxidant activity of DPPH assay among extract with IC50 value of 44.35 mg/mL. In addition, methanol extract also showed the highest antioxidant activity of ABTS assay among extracts with IC50 value of 17.69 mg/mL. This study indicated that the methanol extract of S. polyanthum leaves is potential as antioxidant.